EZH2 Expression and Clinical Outcomes in Non-Small Cell Lung Cancer Patients Treated with Immune Checkpoint Inhibitors: A Real-World Retrospective Cohort Study - Esra Asarkaya; Hatice Asoglu; Abdurrahman Aykut; Gunes Dorukhan Cavusoglu; Yasemin Aydınalp; Sendag Yaslıkaya; Suheda Atas Ipek; Fatma Calkan; Emine Kilic Bagir; Derya Gumurdulu; Hulya Binokay; Tolga Koseci; et al. (Journal of Clinical Medicine, 2026)
Background: Lung cancer remains the leading cause of cancer-related mortality, with non-small cell lung cancer (NSCLC) accounting for approximately 85% of cases. Over the past decade, immune checkpoint inhibitors have become a core component of first-line treatment for advanced-stage NSCLC lacking driver mutations. Programmed death-ligand 1 (PD-L1) expression is currently used as the standard biomarker, yet its predictive value remains limited, and in most immunotherapy trials, treatment efficacy has been observed independently of PD-L1 expression status. Enhancer of zeste homolog 2 (EZH2), an epigenetic regulator, promotes immune escape by suppressing antigen presentation and impairing CD8+ T-cell function, thereby generating an immune-cold tumor microenvironment, positioning it as a promising candidate biomarker. Methods: We retrospectively analyzed 102 NSCLC patients treated with immunotherapy at a single center between 2018 and 2024. EZH2 expression was assessed by immunohistochemistry. A cohort-derived 25% threshold was used for the primary exploratory analysis, and the analyses were repeated using a 50% threshold as a sensitivity analysis. Patients were classified as EZH2-high (45.1%) and EZH2-low (54.9%) at the 25% threshold. Results: At the 25% threshold, objective response rate (ORR) was 53.6% in the EZH2-low group and 45.7% in the EZH2-high group (Fisher’s exact p = 0.551), while disease control rate (DCR) was 64.3% and 60.9%, respectively (p = 0.837). Median overall survival (OS) was 37 versus 27 months (log-rank p = 0.323), and median progression-free survival (PFS) was 15 versus 12 months (p = 0.387). No significant correlation was found between EZH2 and PD-L1 expression (r = 0.167, p = 0.138). In treatment-line-adjusted Cox models, EZH2 expression was not associated with OS (hazard ratio (HR) 0.953, 95% confidence interval (CI) 0.533–1.704; p = 0.870) or PFS (HR 0.996, 95% CI 0.573–1.733; p = 0.989), whereas squamous histology was an independent predictor of survival. Results remained non-significant at the 50% threshold. Early progression was uncommon and did not differ significantly by EZH2 status overall or within PD-L1 strata. Conclusions: In this real-world cohort, EZH2 expression was not independently associated with response, early progression, OS, or PFS, and showed no correlation with PD-L1. These exploratory findings do not support the clinical use of EZH2 as a biomarker at this stage; prospective, multicenter studies using predefined thresholds and standardized immunohistochemical methods are needed to clarify its potential role as a marker complementary to PD-L1.